2016
DOI: 10.1371/journal.pmed.1002118
|View full text |Cite
|
Sign up to set email alerts
|

Association between Adult Height and Risk of Colorectal, Lung, and Prostate Cancer: Results from Meta-analyses of Prospective Studies and Mendelian Randomization Analyses

Abstract: BackgroundObservational studies examining associations between adult height and risk of colorectal, prostate, and lung cancers have generated mixed results. We conducted meta-analyses using data from prospective cohort studies and further carried out Mendelian randomization analyses, using height-associated genetic variants identified in a genome-wide association study (GWAS), to evaluate the association of adult height with these cancers.Methods and FindingsA systematic review of prospective studies was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
46
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 74 publications
11
46
3
2
Order By: Relevance
“…Additionally, there was suggestive evidence of positive associations between height and liver, biliary tract and thyroid cancers. Our findings are consistent with previous MR studies showing a positive association of height with colorectal [50,51], lung [50,52] and breast [53,54] cancer. Increased height is associated with elevated insulin-like growth factor 1 (IGF1), [55] which is a growth factor that drives cellular proliferation and survival and has thus been implicated in carcinogenesis of IGF responsive tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, there was suggestive evidence of positive associations between height and liver, biliary tract and thyroid cancers. Our findings are consistent with previous MR studies showing a positive association of height with colorectal [50,51], lung [50,52] and breast [53,54] cancer. Increased height is associated with elevated insulin-like growth factor 1 (IGF1), [55] which is a growth factor that drives cellular proliferation and survival and has thus been implicated in carcinogenesis of IGF responsive tissues.…”
Section: Discussionsupporting
confidence: 93%
“…A Korea cohort study reported each 5-cm increment in height was associated with increased risk of lung cancer. 13 Similar associations were also recorded in two recent meta-analyses 14,15 ; however, the results from Million Women Study in UK did not find significant associations between height and risk of lung cancer. 16 It remains unclear whether the observed association reflects a causal effect of adult height on lung cancer, or is due to confounding or biases inherent in conventional epidemiological studies.…”
supporting
confidence: 73%
“…Modest association between genetically determined height and risk of lung cancer, based on European population, was reported using MR analysis. Moreover, the increased risk for lung adenocarcinoma appears to be stronger than lung squamous cell carcinoma . Our results are in line with previous observational study in Korean population and the height MR study.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest a 1.10-fold increase in osteosarcoma risk per standard deviation in polygenic height score, which corresponds to an approximately 1.7-cm increase in stature. This can be re-scaled to make direct comparisons with a previous Mendelian randomization study that reported effects sizes per 10-cm increase in genetically-predicted height 45 . While they observed an approximately 10% increased risk of lung cancer, 20% increased risk of breast cancer, and 60% increased risk of colorectal cancer associated with each 10-cm increase in genetically-predicted adult height, our re-scaled estimate is equivalent to a 75% increase in osteosarcoma risk per 10-cm increase in adult height.…”
Section: Discussionmentioning
confidence: 99%